Evaluation report: An assessment of the Diversity for Restoration (D4R) Tool - Wiederkehr Guerra, Gabriela Patricia; Gotor, Elisabetta (2020)
Forest landscape restoration (FLR) can play a key role to revert the loss of forests, while also contributing to an increased well-being of local livelihoods in deforested and degraded landscapes. As we start the UN Decade on Ecosystem Restoration (2021-2030), FLR and ecosystem restoration, in general, are considered an integral part of tackling global environmental and socio-economic challenges. To ensure the short and long-term success of restoration interventions, and meet the ambitious targets, proper planning and guidance at the different stages of restoration are fundamental. In general terms, decision support tools present a great opportunity to guide restoration projects to apply key principles and concepts to ensure a longer-term success. Diversity for Restoration (D4R) is an example of such a decision support tool which specifically helps in species selection and seed sourcing after restoration objectives and site conditions are determined. It integrates different methods to provide suggestions on the best combination of species to use for a given restoration objective (or objectives)andthe site conditions, as well as recommendations on where to collect seeds (i.e., seed zones and seed sources). It also offers propagation information and monitoring suggestions. The present independent assessment aims to evaluate the real potential of the tool via 1) the interest and perception of the tool; 2) the role it can play in strengthening the decision-making process and knowledge transfer of species selection and seed sourcing; and 3) the current impact in knowledge transfer through webinars and workshops